STREAMLINING FINANCIAL DATA PIPELINES FOR CLOUD-NATIVE INDEXING - Tarun Chataraju (IPHO-Journal of Advance Research in Science And Engineering, 2025)
The modern financial services sector faces historic challenges in processing high-speed bond and loan index data against increasinglysophisticated market infrastructures. Cloud-native data pipeline architectures have arisen as revolutionary solutions, allowing financial institutions to handle vast amounts of market data,pricing data, and reference data with considerably lower latencythan conventional on-premises infrastructure.The extraction phase deals with the retrieval of structured and semi-structured data from disparate source systems, whereas the transformation phases invoke advanced business rules, data quality checks, and standardization processes required for analytical consumption. Loading mechanisms move processed data into distributed data lakes and cloud warehouses tuned for analytical query performance. Large cloud platforms offer end-to-end managed ETL services that automate the discovery of data, create transformation code, and manage the execution of jobs through serverless computing paradigms. Best practices in the industry include end-to-end data lineage tracking to meet regulatory needs, strict version control procedures that guarantee reproducibility, and schema validation to ensure data consistency. Real-world deployment examples highlight the imperative need for highly optimized architectures for environments of high-frequency trading, economical partitioning schemes, and strong disaster recovery processes. The shift to cloud-native architectures provides significant cost savings in operations, improved system availability, and unparalleled scaling capabilities that are necessary for today's fixed-income market operations.